Giorgio Agamben: o paradigma do homo sacer e a ex-ceptio da vida nua - Guarnieri, Germano Antonio (2020)
This work aims to address the paradigmatic problem of homo sacer and the ex-ceptio of bare life in the work of the Italian philosopher Giorgio Agamben, which is situated within four thresholds where this question is further developed: a) the concept of Agambean concept of paradigm; b) the political problem of sacredness and the historical relationship between politics and life; c) the problem of bare life and form-of-life; d) the problem of work and the inoperativity. From Agamben’s inventory of concepts based on Aristotelian treaties and archaic Roman law to the definition of “bare life”, to the Agambean’s readings of Hannah Arendt, Yan Thomas, Ernst Kantorowicz, Elias Bickermann, Thomas Hobbes, Odo Casel, Averrois, Dante Alighieri and Walter Benjamin, going through the ultimate reflections of Michel Foucault and Gilles Deleuze, this investigation intends to analyze genealogically the homo sacer figure, identifying it as the first referent and element at stake in politics and the ex-ceptio of bare life as a structure originating in Western politics. Throughout this dissertation, we will be presenting some of the main aporias, implications and antinomies present in Agambean hypotheses and the paradigms that could break with the sacredness of homo sacer and integrate the different forms of life. In addition, we are likely to identify the analogies between the ex-ceptio structure, defined with regard to bare life, and the archè structure in Western culture, which bursts in a multifaceted way in different spheres of Agamben’s philosophy. Finally, this research is concluded with a debate about the concept of puissance destituante (destituent power) to establish its proximity with the Aristotelian power-act device and with the sovereign relationship of ban